Building an Inclusive Literacy Ecosystem for Children through Creative Activities at Kampung Emas UNY - Yudan Hermawan; Nurtanio Agus Purwanto; Siti Rohma Nurhayati; Shely Cathrin; Agus Basuki; Rizqy Aisyah Leonia (Universitas Trunodjoyo Madura, 2026)
The development of an inclusive literacy ecosystem from an early age is a strategic effort to foster a sustainable culture of reading and learning in society. The study aims to illustrate the implementation of a literacy program based on storytelling and coloring activities as a means to enhance children’s literacy interest. The research employed a descriptive qualitative approach involving 25 children aged 5–6 years, parents, student volunteers, and community facilitators. Data were collected through observations, brief interviews, and documentation, and analyzed using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The needs analysis revealed that children had limited exposure to story- and visual-based literacy activities, as well as minimal parental involvement in supporting learning activities at home. The literacy program was implemented in a participatory manner through storytelling and coloring sessions designed to stimulate imagination, improve concentration, and develop children’s expressive abilities. The involvement of student volunteers and community facilitators also strengthened a fun and interactive learning environment. The evaluation results indicate an increase in children’s interest in literacy activities and greater community involvement in supporting child-friendly literacy spaces. These findings suggest that creative, contextual, and collaborative literacy activities can serve as an important foundation for building an inclusive literacy ecosystem within community settings.